Lehrer im Gleichschritt: Der Nationalsozialistische Lehrerbund Hamburg - Schmidt, Uwe 1931-2008 (Hamburg University Press, 2006)
After the National Socialists seized power in Hamburg on March 8, 1933, the existing professional organisations of teachers were first brought together, then dissolved and replaced by the National Socialist Teachers' Association of Hamburg (Nationalsozialistischer Lehrerbund, NSLB), which was founded in 1931, as the only teacher organisation. The primary school teacher Wilhelm Schulz accomplished National Socialist ideology in the largest Hamburg-based teachers' organization, the Society of Friends of the Patriotic School and Education (Gesellschaft der Freunde des vaterländischen Schul- und Erziehungswesens, GdF), founded in 1805. The teacher's organisation ADLV (Allgemeiner Deutscher Lehrerinnenverein - General German Teachers' Association) has been given priority over equalisation through self-dissolution. In 1935, the professional association of senior teachers, the Hamburg Philologists' Association, was forced to dissolve itself under the pressure imposed on it. The NSLB, now the only professional organisation for teachers in Hamburg, was incorporated into the Political Organisation of the NSDAP. After the beginning of the war, the NSLB lost more and more importance. In the course of the "total war" in February 1943 the Hamburg NSLB was also "shut down" for the duration of the war, at the command of the Führer. His story was thus already over two years before the fall of the dictatorship